Social media-assisted interventions on human papillomavirus and vaccination-related knowledge, intention and behavior: a scoping review. Issue 2 (19th March 2022) - Li, Danyi; Fu, Linyun; Yang, Yuanyuan; An, Ruopeng
Abstract: Social media holds the potential to engage adolescents and young adults and to facilitate interventions improving Human Papillomavirus Vaccine (HPVV). This article systematically reviewed the literature on Cochrane Library, PubMed, Web of Science, EMBASE, Scopus and CINAHL. Interventions delivered or facilitated by social media with outcomes of HPV-related knowledge, awareness, attitude, vaccination intention and behavior were included. Standardized forms were used to abstract the basic characteristics, settings, guiding theories and key findings of the interventions. Twenty-four studies met the eligibility criteria. Sixteen were educational interventions, and the other eight investigated the effect of social media message contents on improving Human Papillomavirus (HPV)-related outcomes. The studies were published between 2015 and 2021. The most frequently used social media platforms were Facebook, and the most commonly adopted theory was the health belief model (HBM). Existing interventions have shown preliminary but promising effects in improving HPV awareness and knowledge. Still, such improvements have not always been translated to improved behavioral intentions and vaccination rates. The contents and phrasing of social media messages and pre-existing individual characteristics of social media users moderated intervention effectiveness. Social media could be a valuable tool for engaging participants and delivering HPV interventions. Future interventions should apply stronger theory bases.